Pirolisis Kulit Kayu Pinus Merkusii Menjadi Bio-Oil Menggunakan Katalis Cr/Lempung Cengar - Febrian, Ramadhoni; Bahri, Syaiful; Khairat, Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Bio-oil is produced from biomass through pyrolysis. Then, potential biomass is bark of pine. Bark of pine merkusii can be processed into bio-oil by pyrolysis used Cr/clay catalyst. This research aims to produce bio-oil from bark of pine with Cr/clay catalyst as an alternative fuel, observing the effect of the ratio of catalyst Cr/clay weight to biomass, and observing the influence of Chromium (Cr) impregnation and characterizing physical and chemical characteristic of bio-oil. In the pyrolysis process, 50 grams of pine bark with -100 + 200 mesh, the Cr / clay catalyst with weight variation of the biomass are 3%, 5% and 7% and the variation of Chromium (Cr) impregnation on clay are 0%, 1%, 2% and 3%. And 500 ml of silinap was added to the pyrolysis reactor. Pyrolysis process occurred for 120 minutes at a 320o C and the stirring speed is about 300 rpm. This research resulted in the greatest yield on the use of Cr/clay catalysts 7% of weight to the biomass and 3% metal content is about 65.77%. Characteristics of physical properties was obtained 0.812 g / ml of density, 0.902 cSt of viscosity, 7.626 mg NaOH / gram samples of acidity and 31oC of flash point. While the chemical characteristics of the bio-oil was obtained from the analysis using Gas Chromatography-Mass Spectroscopy (GCMS) and it found several dominant chemical components such as 9,12-Octadecadienoyl chloride, Cyclohexane, 1-methyl-2-penthyl, Octadecanoic acid, 2-Pentene, 24.4-trimethyl and Cyclohexane, 3- (3,3-dimethylbutyl).Keywords: Bio-oil, pyrolysis, bark of pine merkusii, Cr/Clay catalyst